2016
DOI: 10.1136/gutjnl-2016-311861
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 ameliorates alcoholic liver injury by inhibiting the IL-6–p47phox–oxidative stress pathway in neutrophils

Abstract: ObjectivesChronic-plus-binge ethanol feeding activates neutrophils and exacerbates liver injury in mice. This study investigates how recent excessive drinking affects peripheral neutrophils and liver injury in alcoholics, and how miR-223, one of the most abundant microRNAs (miRNAs) in neutrophils, modulates neutrophil function and liver injury in ethanol-fed mice.DesignsThree hundred alcoholics with (n=140) or without (n=160) recent excessive drinking and 45 healthy controls were enrolled. Mice were fed an eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 191 publications
(189 citation statements)
references
References 48 publications
9
176
2
2
Order By: Relevance
“…This is comparable with our finding of a baseline alcohol intake of around 20 UK units of alcohol. A recent study of patients admitted for alcohol detoxification found higher neutrophil counts among those who had been drinking up to the point of admission compared to those who had stopped at least 10 days before admission [15]. In our cohort, we saw a similar effect in the patients who had increased their alcohol intake.…”
Section: Resultssupporting
confidence: 73%
“…This is comparable with our finding of a baseline alcohol intake of around 20 UK units of alcohol. A recent study of patients admitted for alcohol detoxification found higher neutrophil counts among those who had been drinking up to the point of admission compared to those who had stopped at least 10 days before admission [15]. In our cohort, we saw a similar effect in the patients who had increased their alcohol intake.…”
Section: Resultssupporting
confidence: 73%
“…Our recent human data showed that EAU + RD patients had much higher levels of circulating neutrophils, which positively correlated with elevated serum levels of ALT and AST (5). To further explore the underlying mechanism of neutrophilia, particularly in those with recent excessive alcohol drinking, we analyzed serum EVs, MPs, and mtDNA content in 171 EAU patients in whom serum samples were available.…”
Section: Resultsmentioning
confidence: 99%
“…The above human data suggest that recent excessive alcohol (binge) drinking leads to the elevation in the levels of serum mtDNA and circulating neutrophils. To explore the underlying mechanisms, we used a E10d + 1B ethanol feeding mouse model, which mimics the EAU + RD pattern in humans (5). As illustrated in Figure 2A, the number and percentage of circulating neutrophils were also elevated in the E10d + 1B group The total numbers of particles in the sera of healthy control human (control, n = 30), EAU -RD (n = 71), and EAU + RD (n = 100) patients were counted using an NTA system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations